Combination Extract of Lidah Mertua (Sansevieria verticilata) And Sereh (Cymbopogon nardus L.) Indifferent Drying as Anti-Microbial - Rizky Rahadian Wicaksono; Eko Sulistiono (Future Science, 2020)
Sansevieria and Cymbopogon plants are widely available in Indonesia. This plant has many benefits for us. This plant is usually used as a kitchen spice and herbal medicine because of the benefits of the plant. The purpose of this study was to determine the combination extract of Lidah Mertua (Sansevieria verticilata) and Sereh (Cymbopogon nardus L.) in different drying as anti-bacteria as anti-microbial. The method used in this research is true experimental by comparing the control class. The results obtained from this study indicate a combination of Sansevieria and Cymbopogon plant drying 48 hours more effectively inhibits the rate of microbial growth than 24 hours.